Qualitative assessment of local ventilation in Petrochemical Company Laboratories for Reducing Staffs Exposure - Esmaeilzadeh Arezoo; Golbabaei Farideh; Zare Soodabeh (Muhandisī-i bihdāsht-i ḥirfah/ī, 2014)
Background & Objectives : Chemicals are serious harmful agents in the workplace, especially chemistry labs. This material may cause poisoning and different diseases. Laboratory hoods as first safety device protect laboratory workers against hazardous chemicals. This research conducted on chemistry labs in a petrochemical company for awareness of the hoods performance and proposed the needed reforms .